2017
DOI: 10.3390/molecules22111845
|View full text |Cite
|
Sign up to set email alerts
|

Margination of Fluorescent Polylactic Acid–Polyaspartamide based Nanoparticles in Microcapillaries In Vitro: the Effect of Hematocrit and Pressure

Abstract: The last decade has seen the emergence of vascular-targeted drug delivery systems as a promising approach for the treatment of many diseases, such as cardiovascular diseases and cancer. In this field, one of the major challenges is carrier margination propensity (i.e., particle migration from blood flow to vessel walls); indeed, binding of these particles to targeted cells and tissues is only possible if there is direct carrier–wall interaction. Here, a microfluidic system mimicking the hydrodynamic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Polymeric fluorescent nanoparticles (FNPs) based on a fluorescent polyaspartamide-polylactide graft copolymer were synthesized [38,39] and use as drug carrier model. The transport, adhesion and distribution on blood flow of similar particles were previously evaluated to elucidate the FNPs transport toward the vessel vasculature in micro-capillary flow [40]. Here, FNPs were utilized to understand the contribution of the bioreactor perfusion flow to the mobility and distribution of particles inside polymeric scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric fluorescent nanoparticles (FNPs) based on a fluorescent polyaspartamide-polylactide graft copolymer were synthesized [38,39] and use as drug carrier model. The transport, adhesion and distribution on blood flow of similar particles were previously evaluated to elucidate the FNPs transport toward the vessel vasculature in micro-capillary flow [40]. Here, FNPs were utilized to understand the contribution of the bioreactor perfusion flow to the mobility and distribution of particles inside polymeric scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Craparo et al reported a study on a PLA-based nanoparticulate carrier margination in relation to RBC concentration (hematocrit) and pressure drop by using a microfluidic system mimicking the hydrodynamic conditions of human microcirculation in vitro [ 2 ], highlighting the importance of taking into account RBC–drug carrier interactions and physiological conditions in microcirculation when planning a drug delivery strategy based on systemically administered carriers.…”
mentioning
confidence: 99%